2019
DOI: 10.3390/buildings9070157
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Climate Mitigation Effect of Green Roofs—A 20-Year Weather Study on an Extensive Green Roof (EGR) in Northeast Germany

Abstract: Approximately 10 km2 of new green roofs are built in Germany every year. About 85% of these are Extensive Green Roofs (EGR). An EGR with several research features was installed on new buildings belonging to the University of Applied Sciences Neubrandenburg in 1999. The results of the almost 20-year permanent survey of the climate effects of the green roof in contrast to gravel roofs are presented here. High-quality sensors, similar to those used by official weather stations, are in use, and data is collected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Preliminary reports presented the results of the continuous 20-year climate measurements on these roofs. The evidence of the positive influence of the microclimate of the vegetation layer is seen in a significant reduction in the surface temperature [22]. A further paper explains how different retention layers can capture larger volumes of rain in a comparison between conventional growing media and various retention layers.…”
Section: Methodsmentioning
confidence: 96%
“…Preliminary reports presented the results of the continuous 20-year climate measurements on these roofs. The evidence of the positive influence of the microclimate of the vegetation layer is seen in a significant reduction in the surface temperature [22]. A further paper explains how different retention layers can capture larger volumes of rain in a comparison between conventional growing media and various retention layers.…”
Section: Methodsmentioning
confidence: 96%
“…For instance, Peng and Jim [27] and Zhang et al [28] published their work regarding effects of green roofs on the thermal comfort at the pedestrian level. Both papers found a reduction of air temperature at the pedestrian level of around 0.1 to 0.3 • C. Köhler and Kaiser [29] present evidence that green roofs contribute to mitigation of climate change. But other authors did not find relevant effects on thermal comfort [30,31].…”
Section: Introductionmentioning
confidence: 94%
“…Zhang et al [28] found a reduction of air temperature at the pedestrian level of 0.1 to 0.3 • C. Both support and approve the findings of the presented paper. Ng et al [29] as well as Rosenzweig [31] in contrast concluded that green roofs have only a neglectable influence on the thermal comfort at the pedestrian level. One has to bear in mind that they derived their findings from simulations performed for areas dominated by high rise buildings, compared to Elief Playhouse.…”
Section: Urban Challenge Of Climate: Thermal Comfort On Pedestrian Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahora bien, en la figura 11 se destaca un diferencial mucho más notorio que en los demás: si bien el ladrillo sigue por encima de los demás materiales de estudio, el jardín por el contrario tiende a una temperatura similar a la del ambiente, por lo cual no acumula tanta radiación a lo largo del tiempo. El estudio de Kaiser y Köhler [37] afirma que la implementación de coberturas vegetadas como aislantes térmicos controla el efecto isla de calor.…”
Section: Descripción Por Temporadasunclassified